The interplay between physical exercise and autophagy signaling in brain health, neurodegenerative diseases and aging - Gao, Bo; Wang, Li; Gong, Jian; Zhu, Zehua; Liu, Qi; Yuan, Han; Wang, Haitao (Frontiers in Aging Neuroscience, 2025)
Brain health is increasingly recognized as a critical component of overall wellbeing, particularly concerning neurodegenerative diseases, which are characterized by the progressive degeneration of the nervous system. Conditions such as Alzheimer’s disease (AD) and Parkinson’s disease, together with less common disorders, resembling Amyotrophic lateral sclerosis (ALS), and Huntington’s disease (HD), significantly impact cognitive and physical health, affecting over 50 million individuals worldwide. This review explores the multifaceted relationship between brain health and neurodegeneration, emphasizing the roles of biological, environmental, and lifestyle factors. Notably, physical activity has been identified as a potent intervention that enhances neuroplasticity and metabolic resilience while mitigating the effects of neurodegeneration. Research indicates that exercise activates autophagy, which is crucial for clearing neurotoxic aggregates like amyloid-beta and α-synuclein, thereby promoting neuronal health. Additionally, exercise stimulates the production of neurotrophic factors such as BDNF and GDNF, which are essential for neuronal survival and function. Despite the promising findings regarding exercise as a preventive and therapeutic strategy for neurodegenerative diseases, further investigation into the underlying mechanisms is necessary to optimize these interventions. This review aims to elucidate the complex interactions between exercise, autophagy, and brain health to provide insights into effective strategies for combating neurodegeneration.